A Model of Academic Social Responsability - Alina Mihaela DIMA; Simona VASILACHE; Valentina GHINEA; Simona AGOSTON (Transylvanian Review of Administrative Sciences, 2013)
This paper develops the idea of academic social responsibility derived from the corporate social responsibility, presents the main achievements of the Romanian higher education system from the perspective of social responsibility and proposes a model of social responsibility in universities based on six dimensions determined by extensive literature review and content analysis.